Titanium(IV)-EDTA complex - Kinetics of thermal decomposition by non-isothermal procedures - Guinesi, Luciana S.; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Santos, A. F.; Capela, Marisa Veiga [UNESP] (Springer, 2006)
This work aims the evaluation of the kinetic triplets corresponding to the two successive steps of thermal decomposition of Ti(IV)-ethylenediaminetetraacetate complex. Applying the isoconversional Wall-Flynn-Ozawa method on the DSC curves, average activation energy: E=172.4 +/- 9.7 and 205.3 +/- 12.8 kJ mol(-1), and pre-exponential factor: logA = 16.38 +/- 0.84 and 18.96 +/- 1.21 min(-1) at 95% confidence interval could be obtained, regarding the partial formation of anhydride and subsequent thermal decomposition of uncoordinated carboxylate groups, respectively.From E and logA values, Dollimore and Malek methods could be applied suggesting PT (Prout-Tompkins) and R3 (contracting volume) as the kinetic model to the partial formation of anhydride and thermal decomposition of the carboxylate groups, respectively.
Keywords: activation energy; kinetic model; non-isothermal kinetics; Ti(IV)-EDTA; TiO2